Pathways into sexual exploitation and sex work: the experience of victimhood and agency - Dodsworth, Jane (Palgrave Macmillan, 2015)
Acknowledgements -- Introduction -- Pathways through sex work : historical, legislative and theoretical perspectives -- Selling sex : an historical, legislative and policy perspective -- Routes into sex work : who, why and how? -- Managing involvement in selling sex : staying, leaving, surviving -- Pathways through sex work : experiences of victimhood and agency -- Managing the coexistence of roles and identities -- Group one : "Who I am" -- Group two : "What I do" -- Group three : "Not for me" -- Resilience and agency -- References